Can Experiences of Authentic Scientific Inquiry Result in Transformational Learning?. (October 2013) - Walker, Tracy; Molnar, Tim
This work examines the experience of secondary school students involved in authentic science inquiry (ASI) at the Canadian Light Source. We suggest this experience is a transformational learning experience for participants. Using evidence from surveys and interviews from a total of 119 high school students, 23 teachers, and 18 scientists participating in the Students on the Beamline project during 2007–2010, we employ a transformational learning theory framework (Cranton, 2002; Mezirow, 1997a, b; Imel, 1998) in an interpretive approach to determine the extent this experience is transformative. Discussions of ASI and transformational learning are provided. Our investigation suggests that transformational learning can occur through such learning activity highlighted, for example, by changes in student perceptions of scientists, perceptions of themselves as capable of sophisticated science investigation, and considerations of science as a future life endeavour.